Performability in Internet of Things - Al-Turjman, Fadi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses the challenges in the convergence of technologies as the Internet of Things (IoT) evolves. These include sensing, computing, information processing, networking, and controlling intelligent technologies. The contributors first provide a survey of various assessment and evaluation approaches available for successful convergence. They then go on to cover several operational ideas to apply. The contributors then discuss the challenges involved bridging gaps in computation and the communication process, hidden networks, intelligent decision making, human-to-machine perception and large-scale IoT environments. The contributors aim to provide the reader an overview of trends in IoT in terms of performability and traffic modeling and efforts that can be spent in assessing the graceful degradation in IoT paradigms. Provides a survey of IoT assessment and evaluation approaches; Covers new and innovative operational ideas that apply to the IoT industry and the industries it affects; Includes chapters from researchers and industry leaders in IoT from around the world.
Chapter1: Performability Analysis Methods for Clustered WSNs as Enabling Technology for IoT -- Chapter2: Practical Performability Assessment for Zigbee-based Sensors in the IoT Era -- Chapter3: Evaluation of Simulation Approaches and Need for MDE in Energy Effeciency, Performance and Availability Assessment of IoT -- Chapter4: False Data Injection Attacks in Internet of Things -- Chapter5: Energy Efficient Clustering forWireless Sensor Devices in Internet of Things -- Chapter6: Toward optimum topology protocol in health monitoring -- Chapter7: Internet of Things (IoT) Considerations, Requirements, and Architectures for Disaster Management System -- Chapter8: Internet of Things and Statistical Analysis -- Chapter9: Internet of Vehicle (IoV) Applications in Expediting the Implementation of Smart Highway of Autonomous Vehicle: A Survey -- Chapter10: Virtual Coordinate Systems and Coordinate-based Operations for IoT -- Chapter11: Small Data in IoT: An MCS Perspective.
Keywords: Telecommunication; Application software; Electric power production; Database management; Signal processing; Communications Engineering, Networks; Computer and Information Systems Applications; Electrical Power Engineering; Database Management; Signal, Speech and Image Processing